Random Number Generator with Long Cycle Based on Memory Cells - Noman Alassali, Saleh; Mansour AL-Aqelee, Hameed (International Journal of Computer Sciences and Engineering, 2021)
Nowadays, random numbers become essential element in many activities. Random numbers can be used in several applications, like simulations, security systems, managements, financial operations, and so on. Indeed, there are many of random numbers generators ‘RNGs’ currently in used, but so far, there is no ideal one, and the requirement of RNGs are increased while the passed time. The main defects in the available RNGs are the short period of its repeat cycle length and also the predefined values of static factors as well. This research will try to suggest a method to extend the periodic cycle of the repetition, and to improve the quality of the generated numbers randomly. The main idea of this research is to build spherical structure to become memory cells that contain initial random numbers, using a combination of two linear congruently generators. Every cell contains one number. Generating any random number takes place by determining the memory cell index found on spherical structure and make the generation of any random number affects the values of many cells of its neighbors, and also affected by the values of many cells randomly. The spherical structure can be represented by three dimensions matrix, with suitable sizes’ not less than 10, 10, 10,.